Prediction of time diversity gain for earth-to-satellite microwave link design based on real time rain intensity measurement - Alam, Md Moktarul; Islam, Md Rafiqul; Koohestani, Mohsen; Elsheikh, Elfatih A A (IEEE, 2023)
The propagation impairments by rain strongly affect the earth-to-satellite links operating at frequencies higher than 18 GHz mainly due to the severe performance degradation of satellite communication system. The time diversity technique with appropriate time delay between successive transmissions has been found effective in mitigating the rain fade. However, time diversity analysis demands measured rain attenuation data, where the latter is unavailable at most of the places to be able to design future high frequency links. The time diversity gain prediction model has been found to be robust for time diversity improvement. Here, we propose a new model for the rain rate with and without the time delay considering the three variables of rain rate, time delay and frequency. The rain rate and time delay functions were first used to derive the constants by the regression from the rain rate and rain rate gain. The constant for the frequency function was then extracted from the cumulative distribution function of the attenuation predicted by the analytically obtained ITU-R and gain equations. The proposed model was validated using one-year rain rate and attenuation data measured at two different locations in Malaysia demonstrating a 7% prediction inaccuracy when compared to the existing models, therefore, it can be reliably used for future earth-tosatellite link designs by using measured rain rate at any higher frequencies.